DEVELOPMENT OF WAQF LAND IN MALAYSIA: A CURRENT REVIEW IN STATE OF PULAU PINANG - Nur Afiqah Anuar; Nor Nadirah Akmar Mokhtar; Muhammad Azwan Sulaiman; Muhammad Nazim Alias; Nurul Nadiah Zainol (Journal of Islamic, Social, Economics and Development, 2022)
In Malaysia, waqf matter is managed by an institution as a trustee such as State Islamic Religious Council. This council will plan and manage the waqf land according to specific deed, either for general or specific waqf deed as prescribed by the person who waqf the asset. However, waqf lands are still not being fully unutilized thus affecting the performance of waqf land development. A qualitative approach was conducted with four respondents in order to obtain to identify the current waqf land development in Pulau Pinang. The data received has been analysed through content analysis method. the research outcome shown the waqf development in Pulau Pinang had continuous development from Wakaf Seetee Aisah to Wakaf Seetee Aisah 2. The development is expected to have about 422 units of medium cost apartment, 150 units of low-cost apartment, 30 units of shop-offices, 15 units of stall centres, office blocks (4 storeys), surau and halls which estimated to cost about RM 120 Million.